Forming Independence in Young Children Through The Habituation Method - Irhamna Irhamna; Elvi Mardiana; Khamin Zarkasih Putro; Na'imah Na'imah (JOYCED: Journal of Early Childhood Education, 2022)
This study aims to examine the method of habituation in getting used to the attitude of independence in early childhood in Malahayati Kindergarten, which can be seen in the early days of schooling early childhood in school have behavior that cannot be separated from parents and the existence of bad attitudes that exist in children when children at home, then through this study the researchers wanted to see how the adoption of the habituation method applied in Malahayati Kindergarten in shaping the attitude of independence in children. The type of research used in this study is qualitative research with a descriptive approach. Furthermore, the data collection tools used are interviews aimed at class teachers as those who plan and implement learning activities for children and observations aimed at class B children with documentation as complementary data. The research results show that the formation of independence in children with the habituation method can change children's behavior with the help of teachers who become role models.